Sociální podnikání jako nástroj udržitelnosti poskytování sociálních služeb - Šebestová, Jarmila (Univerzita Pardubice, 2012)
Available offer of social services within optimal budget there is a challenge facing society and municipalities nowadays. One possible way is to cooperate with non-profit sector to share the same goal through social business unit. Social enterprises are highly differentiated depending on the needs of their target populations, and their program and financial objectives. They combine entrepreneurial and direct employer principles to provide business and get resources without any other support. Social enterprise revenues must cover normal business operations as well as subsidize social program costs incurred by working with its target population. The main goal of this paper is to present recent trends and models of social business units suitable for social services providing. The case study is presented as a practical picture of model using in contrast with student knowledge about social entrepreneurship according small survey. Finally paper highlights that social enterprise programs uses modified private-sector business tools and puts viability at the forefront as the means to achieve social impact.
Social entrepreneurship as possibile way for suistainable social services
Keywords: social impact; services; target group; disable people; sustainability